20.6k views
1 vote
Help! I do t understand

Help! I do t understand-example-1

2 Answers

7 votes

Answer:

The correct answer is second option 2

(f o g)(x) = 2

Explanation:

It is given that,

f(x) = x and g(x) = 2

To find (f o g) (x)

We have f(x) = x and g(x) = 2

we can write (f o g)(x) as

(f o g)(x) = f(g(x))

g(x) = 2

f(g(x) = f(2)

f(x) = x

f(2) =2

Therefore the correct answer is second option 2

User Anomaaly
by
4.8k points
4 votes

Hello!

The answer is: The correct option is the second option, 2.

Why?

We are working with composite functions. Composite functions mean to evaluate a function in another function.

Composite function:


(f\circ g)(x)=f(g(x))

So, for this case, where there is a variable "x" we need to rewrite it with the function g(x)

Then,


(f\circ g)(x)=(g(x))=(2)\\(f\circ g)(x)=2

Hence, the correct option is the second option, 2.

Have a nice day!

User MikeVaughan
by
5.4k points